Physical Activity Frequency and Mental Health in Old Age: A Bidirectional Association - Juhendra Juhendra; Rita EkaIzzaty; Yoga Setyo Wibowo (Universitas Ahmad Dahlan, 2020)
The association between physical activity and mental health have been found bidirectional in the literature. However, evidence of this bidirectional association is lacking from developing countries. This study was aimed at investigating the bidirectional relationship between physical activity frequency and mental health in old age using data from the Indonesia Family Life Survey with a sample of 8,323 old individuals aged between 45 and 90 years.Â The results revealed that the bidirectional association holds true in old age. Specifically, an increase of one unit in frequency of physical activity is associated with a decrease of 14% in depression after controlling for a set of confounding variables. Similarly, an increase of one unit in depression is associated with a decrease of 3.4% in frequency of physical activity. The results of this study suggest that health policies should take into account the importance of the frequency of physical activity.Keywords: frequency of physical activity, mental health, depression, old age, Indonesia